Dynamic contracts when agent's quality is unknown - Boyan Jovanovic; Julien Prat (Theoretical Economics, 2014)
We solve a long-term contracting problem with symmetric uncertainty about the agent's quality, and a hidden action of the agent. As information about quality accumulates, incentives become easier to provide because the agent has less room to manipulate the principal's beliefs. This result is opposite to that in the literature on "career concerns" in which incentives via short-term contracts become harder to provide as the agent's quality is revealed over time.
Keywords: D82; D83; E24; J41; 330; Principal-agent model; optimal contract; learning; private information; reputation; career